EXPLORING THE LIVED EXPERIENCES OF SEASONALLY UNEMPLOYED PARENTS IN THE GOUDA AREA - Izaks, Fredeline; Avenant, Jana; Van Schalkwyk, Izanette (Social Work/Maatskaplike Werk, 2018)
The aim of this qualitative study was to explore and describe the lived experiences of seasonally unemployed parents in the Gouda area of the Western Province. Positive psychology provided the theoretical framework. A qualitative descriptive research design was used and seven adult parents were selected purposefully. Thematic data analysis focused on the inductive coding of collected data. Findings indicate that seasonally unemployed parents experience periods of employment and unemployment as distinctly different. Yet their experiences during periods of being employed or not are described as a series of challenges varying in degrees of difficulty for parents and their children.